Plasma Astrophysics, Part II Reconnection and Flares - Somov, Boris V. (Astrophysics and Space Science Library,, 2007)
This well-illustrated monograph is devoted to classic fundamentals, current practice, and perspectives of modern plasma astrophysics. The first part is unique in covering all the basic principles and practical tools required for understanding and working in plasma astrophysics. The second part presents the physics of magnetic reconnection and flares of electromagnetic origin in space plasmas within the solar system; single and double stars, relativistic objects, accretion disks, and their coronae are also covered. This book is designed mainly for professional researchers in astrophysics. However, it will also be interesting and useful to graduate students in space sciences, geophysics, as well as advanced students in applied physics and mathematics seeking a unified view of plasma physics and fluid mechanics.